Evaluation De La Diversité Et Estimation De La Biomasse Aérienne Des Arbres Du Jardin Botanique De Bingerville (District d’Abidjan, Côte d’Ivoire) - Oulaïtar, Monssou Eugène; Aimé, Vroh Bi Tra; Bertin, Goné Bi Zoro; Yves, Adou Yao Constant; Edouard, N’Guessan Kouakou (European Scientific Journal, ESJ, 2016)
The Bingerville Botanical Garden is an urban green space which can contribute to the quality of the living environment and to attractivity of tourists in Abidjan city. Its floristic diversity and socio-economic and ecological benefits remain still unknown. The present study was conducted to assess botanical species diversity and the reduction of CO2 emissions in this space. Trees species with dbh ≥ 10 cm were recorded in 41 plots of 500 m² surveyed in four types of biotopes: two arboretums with 20 and 100 years old, one secondary forest with more than 100 years and a fallow of 20 years old. Floristic indices and aboveground biomass (AGB) were determined for each biotope. A total of 742 trees with dbh ≥ 10 were counted: 127 species. Preponderance species are Cassia siamea, Terminalia mantaly, Milicia excelsa and Ceiba pentandra in arboretums, Pentadesma butyracea and Acacia mangium in the secondary forest, Ficus exasperata and Borassus aethiopum in the fallow. Arboretums are richest (96 species), and they have more AGB (566.7 t/ha). The secondary forest has 71 species with an aboveground equal to 381.4 t/ha. The fallow is less rich (13 species) with an AGB of 21 t/ha. This study has shown the importance of Bingerville Botanical Garden in plant and fighting against climate change.